2021
DOI: 10.26508/lsa.202000979
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages-induced IL-18–mediated eosinophilia promotes characteristics of pancreatic malignancy

Abstract: Reports indicate that accumulated macrophages in the pancreas are responsible for promoting the pathogenesis of chronic pancreatitis (CP). Recently, macrophage-secreted cytokines have been implicated in promoting pancreatic acinar-to-ductal metaplasia (ADM). This study aims to establish the role of accumulated macrophage-activated NLRP3-IL-18-eosinophil mechanistic pathway in promoting several characteristics of pancreatic malignancy in CP. We report that in a murine model of pancreatic cancer (PC), accumulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…This treatment regimen was reported to elicit pancreatic neoplasia [ 37 ] and is based upon the notion that combining the effect of carcinogens with chronic inflammation elicits tumor initiation and growth [ 38 ]. Given the severe morphological alterations of Hpa2-KO pancreas we, nonetheless, reduced the frequency of cerulein treatment from three consecutive days [ 37 ] to only once per week (Fig. 7B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment regimen was reported to elicit pancreatic neoplasia [ 37 ] and is based upon the notion that combining the effect of carcinogens with chronic inflammation elicits tumor initiation and growth [ 38 ]. Given the severe morphological alterations of Hpa2-KO pancreas we, nonetheless, reduced the frequency of cerulein treatment from three consecutive days [ 37 ] to only once per week (Fig. 7B ).…”
Section: Resultsmentioning
confidence: 99%
“…Chronic pancreatitis ( CP) was induced by repetitive intraperitoneal (i.p) administration of cerulein without or with azoxymethane (AOM), each alone and in combination, as described elsewhere [ 37 ]. AOM (10 mg/kg) was administrated i.p in 0.1 ml saline; Cerulein (50 μg/kg) was given by repetitive 6 hourly i.p injections, in 0.1 ml saline, as reported [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Among the downregulated BPs, IL-18, cellular response to fibroblast growth factor stimulus, and sphingolipid biosynthetic process were significantly affected (Figure S25B). Previous studies reported that IL-18 and sphingolipid metabolism played important roles in promoting the occurrence and development of PC. In summary, these RNA-seq results indicated that the influence of D4 Nb-PCP NPs plus light irradiation on PDAC cells or TME involved a complex regulatory network and multiple molecular mechanisms of action, which might inhibit tumor progression by affecting tumor biosynthesis, metabolic response, and immune regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Sections of paraffin-embedded mouse esophagus tissue (5 m) were deparaffinized and dehydrated, and staining was performed as previously reported 53 . Antigen retrieval was performed using the Citric Acid-based Antigen Unmasking Solution (Vector labs) method, followed by blocking with 5% normal goat serum to reduce non-specific binding and incubation with specific primary antibodies: anti-F4/80 (1:200, Cell Signaling Technology, 30325S); Rabbit anti-NLRP3 (1:200, Cell Signaling Technology, 15101S); anti-IL-18 (1:200, Invitrogen, HL1859); anti-Cytokeratin antibody (1:400, Cell Signaling Technology, 4545).…”
Section: Methodsmentioning
confidence: 99%